Empowering Coastal Communities Through the "Sinari Tebet Jaya" (Sinergi Kolaborasi Terintegrasi Ternak Bebek Taret Jaya) Food Security Program in Air Anyir Village, Bangka - Sudarya, Albaari Rahman Hakim (Prospect: Jurnal Pemberdayaan Masyarakat, 2024)
Abstract "Sinari Tebet Jaya" program, initiated by PT PLN Nusantara Power Services Unit PLTU Bangka, aims to enhance community welfare in Air Anyir Village by providing alternative income sources through integrated poultry farming. The program addresses local economic challenges and environmental concerns by focusing on duck farming, organic waste utilization, and developing environmentally friendly businesses. This study employs a qualitative approach with active participation and direct observation methods, involving interviews and fieldwork conducted from June to July 2024. The results indicate that the program has significantly improved the economy of the Taret Jaya group by fostering awareness of organic waste management and enhancing local business capabilities. The integration of duck farming with agricultural practices and UMKM development has positively impacted social, economic, and environmental aspects. The program has also supported sustainable business practices, demonstrating its effectiveness in promoting environmental stewardship and economic resilience in Air Anyir Village.